Perceptions and reported use of extended reality technology in Royal College-Accredited Canadian Simulation Centres: a national survey of simulation centre directors - Junko Tokuno; Elif Bilgic; Andrew Gorgy; Jason M Harley (Canadian Medical Education Journal, 2024)
Background: Extended reality technology (XR) in simulation-based medical education is becoming more prevalent. This study examined Canadian simulation centre directors’ perceptions toward XR and their self-reported adoption of XR within their centres.